What Drives Household Borrowing and Credit Constraints? : Evidence from Bosnia and Herzegovina - Chen, Ke.; Chivakul, Mali. (Washington, D.C. : International Monetary Fund, 2008)
Although Bosnia and Herzegovina (BiH) has experienced rapid growth in credit to households in recent years, most individuals are still credit constrained. This paper analyzes the determinants of household credit demand and credit constraints in BiH. To our knowledge, it is the first study on this topic employing household survey data (2001 and 2004) from Emerging Europe. Our results highlight the impact of the post-conflict and transitional nature of the country on the behavior of borrowers and lenders. As expected, age, income, wealth and education qualifications are the main factors driving credit market participation, while high income and high wealth lower credit constraints. In BiH, the probability of credit market participation peaks at 45 years old, considerably higher than in the advanced countries. At the same time, older individuals are significantly more constrained than their peers in the advanced countries. The results imply that the current credit boom may largely reflect the overall post-war demand, and indicate the worse-off position of the older generation in transition economy. Moreover, the results underscore the structural nature of unemployment as well as the mismatch between education qualifications and earning prospects in BiH. Education variables have no significant effect on the likelihood of being constrained, while, unlike in the advanced countries, being unemployed significantly increases the likelihood.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet